The influence of the different content of protein fractions in sows’ milk in piglet rearing - Ewa Skrzypczak, Karolina Szulc , Monika Demkowicz , Damian Knecht, Anna JankowskaMąkosa , Janusz T. Buczyński; Marek Babicz (African Journal of Pig Farming, 2020)
The aim of this study was to investigate the influence of the percentage content of protein fractions in total protein of sow`s colostrums and milk and their influence on the traits related with piglet rearing. The animal specimens were 20 sows of the native Złotnicka White breed. Złotnicka pigs were subjected to the National Genetic Resources Conservation Programme. Colostrum and milk were collected between the 20th and 24th h after parturition and on the 2nd, 3rd, 7th, 14th and 21st day of lactation. A total of 120 samples (60 colostrum samples and 60 milk samples) were collected from all active mammary glands. Individual fractions of total protein were separated by means of electrophoresis on polyacrylamide gel in the presence of sodium dodecyl sulphate (SDS). The piglets’ body weights average daily gains and mortality were checked consecutively after 24 hours after parturition and on the day 7th, 14th, and 21st of lactation. 207 piglets were examined. A highly significant correlation between the number of piglets, daily growths and protein fractions was observed. The most favourable rearing results were obtained at the highest level (III) of individual fractions. The study also proved most of the piglets are lost from the litters when the level of fractions is the lowest (I).